Pengaruh Rasio Keuangan bagi Perubahan Laba pada Perusahaan Manufaktur Sub Sektor Farmasi Teregistrasi BEI Periode 2019-2021 - Aulia Nur Fitriana; Ahmad Budiman (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2023)
The aim of the research is to provide a more specific and relevant understanding of the influence of financial ratios on profit changes in the context of registered Pharmaceutical Sub-Sector Manufacturing Companies in the period 2019-2021. The financial ratios measured include CR (Current Ratio), DER (Debt-to-Equity Ratio), TATO (Total Asset Turnover), and NPM (Net Profit Margin). The research follows a quantitative method. The population consists of all pharmaceutical sub-sector manufacturing companies (11 companies). A sample of 8 companies was selected using purposive sampling method. The sample selection criteria were (a) registered on the Indonesia Stock Exchange in the period 2019-2021; (b) having complete financial statements as required. The data used are secondary data, namely annual financial reports sourced from the Indonesia Stock Exchange website. The data were analyzed using descriptive statistics, classical assumptions, multiple linear regression test, F-test, t-test, and R-square test. The research findings are as follows: (1) CR has a significant positive impact on profit changes with a significance level of 0.02 (sig<0.05); (2) DER has a significant positive impact on profit changes with a significance level of 0.01 (sig<0.05); (3) TATO has a significant positive impact on profit changes with a significance level of 0.01 (sig<0.05); (4) NPM has a significant positive impact on profit changes with a significance level of 0.03 (sig<0.05); (5) CR, DER, TATO, NPM simultaneously have a significant positive impact on profit changes with a significance level of 0.01 (sig=0.01<0.05). Keywords: financial ratios, profit changes, pharmaceutical companise